Presence of eimerid oocysts in faeces of a quarantined dog in Iceland is explained by coprophagic behaviour prior to its importation. Case report - Karl Skírnisson; Donald W. Duszynski (BMC Veterinary Research, 2020)
Abstract Background All dogs imported into Iceland must undergo mandatory quarantine in a special station before introduction into the country. A faecal sample is collected from the first stool passed by the dog in this station and subsequently examined for the presence of intestinal parasite stages. Case presentation In May 2019 unsporulated oocysts were detected in faeces from a 7-year-old household dog that had been imported from Sweden. Most of the oocysts studied strongly resembled those of Eimeria canis Wenyon, 1923. As this species is not valid, the purpose of the present article was to identify the correct species and examine their possible origin. Studies confirmed the presence of two distinct unsporulated oocyst morphotypes in the faeces; measurements and photomicrographs confirmed their identification as Eimeria magna Pérard, 1925 and Eimeria stiedai (Lindemann, 1865) Kisskalt and Hartmann, 1907, both common parasites of European rabbits, Oryctolagus cuniculus (L., 1758). When the owner of the dog was questioned about the food administrated to the dog prior to its import to Iceland, it turned out that it had exclusively been fed dry dog food pellets. However, the owner also reported that on the morning prior to transportation to Iceland, the dog was allowed to move freely in a grassland area where rabbits are common and heaps of their faeces are present. Furthermore, the owner confirmed that the dog consumed rabbit faeces that morning. Conclusion It is believed that this coprophagic behaviour can explain the detection of rabbit eimerids in the dog’s faeces, and that such behaviour must be taken into consideration by veterinarians and other diagnostic personnel when they detect atypical cysts or eggs during coprological examinations.